Moving to Greener Pastures? Multinationals and the Pollution Haven Hypothesis - Eskeland, Gunnar A. (Working Paper Series (National Bureau of Economic Research), 2002)
This paper presents evidence on whether multinationals are flocking to developing country 'pollution havens'. Although we find some evidence that foreign investors locate in sectors with high levels of air pollution, the evidence is weak at best. We then examine whether foreign firms pollute less than their peers. We find that foreign plants are significantly more energy efficient and use cleaner types of energy. We conclude with an analysis of US outbound investment. Although the pattern of US foreign investment is skewed towards industries with high costs of pollution abatement, the results are not robust across specifications.